The Rathbone Hotel: internship report - Faleiro, André Ludgero Soares Raposo Pires (2021)
In order to complete their studies for their Master’s Degree in Hospitality Management at the University of Algarve, students were given several options: to write a thesis; develop and put into practice a project or to do an internship and present a final report. Bearing in mind that I was looking for a challenge, I decided to do a one-year internship abroad, namely, at The Rathbone Hotel, a boutique hotel in London, to acquire more practical experience in the hospitality industry and to hone the skill sets I acquired during my course, so that I could become a better professional in my area of expertise. The fact that Rathbone Hotel is a boutique hotel greatly influenced my choice, as I have always had a particular interest in better understanding what this concept truly means. This interest derived from having a preference for this style of hotel, as a customer (which, after all, is at the heart of the hotel industry, “everything is because of the guest, his perception and how he feels!!!”). As I already had the perception of being a customer in several boutique hotels, I wanted to learn and understand how they work and function on the other side of the barricade, as an employee and future manager. After going through a selection process, we developed an internship plan in collaboration. This plan had all the data regarding the functions I would perform in each operational department of the hotel, as well as the scheduled length of time I would spend in every department. I started my internship working in Reservations. Afterwards, I went to Housekeeping, Food and Beverage – Breakfast Service, Accounts, Front Office – Reception, Food and Beverage – Bar and Room Service and I completed my internship as a Duty Manager. The main objective of this internship (and how it was outlined) focused on the acquisition and application of knowledge regarding hotel management and operation, namely with regards to the planning, execution, optimization, control and monitoring phases, in an attempt to improve processes and to develop skills in the hospitality industry. During my internship, I developed and acquired several skill sets, performing several tasks in all of the hotel´s departments, I did specific reports under management’s requests, I met many people and developed a solid network, I learnt, and I became a Rathbone Hotel family member. I successfully completed all the tasks I was assigned, according to their deadline and to the hotel´s standards. The opportunity to work at The Rathbone Hotel (and in almost all of its departments, without going through the Maintenance department - for security reasons) provided me with ample opportunities, not only for learning, but also for exposing knowledge acquired through the Master’s in Hospitality Management course, by working and performing my duties as an extremely competent hospitality professional. During the internship period, I developed several essential skills, such as solving the most diverse queries and real problems (in real time, in front of a guest). I believe that there could be no better way to test our knowledge and our ability to respond to different requests, since in the professional world everything works differently. I had immense opportunities to put my theoretical knowledge into practice, having participated in several strategic meetings, where I shared my knowledge and points of view regarding the performance of the various departments of The Rathbone Hotel. At the end of each stage of my internship, a meeting was held with the participation of the Hotel Manager (Mr. Miguel Silva), the General Manager (Mr. Daniel Harris) and myself. In these meetings, I presented my conclusions about the various departments to both (strengths, weaknesses and points to improve), something that made me feel, more and more, as a valuable member of the hotel team. After this first meeting, a second meeting was scheduled with the person responsible for each department to outline an action plan, in order to correct some existing problems and to optimize the functioning of each department and the hotel, as a whole. This report chronicles my one-year experience as an intern at The Rathbone Hotel, starting with a brief description of the company, the unit´s characterization, an internal and external analysis (SWOT) and a brief analysis on BREXIT´s possible impacts on the United Kingdom´s tourism. Then, there´s a thorough description of all of the hotel´s departments and of all of the tasks I was assigned, as well as a description of the issues I found during my internship and their possible solutions. As an advanced research, I developed Standard Operational Procedures for the Accounts department and, finally, on the last chapter, we can find my concluding remarks about my internship. I think that the choice to have done this internship was one of the best choices I could have made. Not only did I grow a lot, as a professional and as a person, but I was also able to see, first-hand, the functioning of a boutique hotel, in the centre of one of the busiest cities in the world. I learnt the correct way to communicate with guests and how to maintain a close relationship with them, without ever losing professionalism and posture. Even to this day, I believe that being able to reconcile these behaviours is one of the best feelings in my line of work. All of these guidelines have helped me to become the professional I am today and will help to shape the professional I want to be in the future. I would like to end this section by saying that I strongly advise all students to pursue a curricular internship of this nature for several reasons. The first is related to the fact that they will manage to reconcile all the theoretical knowledge learnt during the Master’s course in Hospitality Management at the University of Algarve with the practical knowledge that they will develop. The second reason is related to the fact that it is an extremely valuable professional experience, that is, even if they already have a good practical knowledge (e.g. they already work in the industry), this experience will force them to expand their horizons, to leave their comfort zone and ultimately acquire new knowledge that can be applied in their future professional life. Lastly, but not least, it will enrich them on a personal level, due to all the situations experienced as a result of the internship.